Building Collaboration, Solidarity, and Empowerment for Enterprise Actors in Yogyakarta City, Indonesia: Towards an Adaptation of Digital Platforms - Izudin, Ahmad; Fittaqiya, Sheima (Prosperity: Journal of Society and Empowerment, 2024)
This article attempts to identify the role of communities in transforming economics in the digital age. A case study approach was selected in Yogyakarta City to understand the changing roles of local people in technological advancements. The findings of this research illustrate that the government initiative program, known as “Gage” (Gandeng-Gendong), has evolved into a new space of mediatization for developing entrepreneurial activities through a digital platform. The stakeholder initiation also contributes to the solidity of community bonding by engaging local businesses in developing the incubator entrepreneur, leading to more effective product adaptation to meet consumer needs. It is important that the involvement of three key stakeholder roles, such as Academicians, Businesses, and Government (ABG), be actively integrated into developing digital platform users. This study has evaluated the conflict between human roles and technological advancements. If our understanding of human beings fails to adapt to digital media and illiteracy persists, it could lead to alienation. However, effectively managing enterprise platforms through e-commerce and collaborative pathways can be viewed as a new asset in fostering community development on a larger scale.